Adaptive Emotional Personality Model based on Fuzzy Logic Interpretation of Five Factor Theory - Mustafa, Ahmed; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Hameed, Shihab A. (2008)
In recent years, emotional personality has found an important application in the field of human machine interaction. Interesting examples of this domain are computer games, interface agents, human-robot interaction, etc. However, few systems in this area include a model of personality, although it plays an important role in differentiating and determining the way they experience emotions and the way they behave. Personality simulation has always been a complex issue due to the complexity of the human personality itself, and the difficulty to model human psychology on electronic basis. Current efforts for emotion simulation are rather based on predefined set or inputs and its responses or on classical models which are simple approximate and have proven flaws. In this paper an emotional simulation system was presented. It utilizes the latest psychological theories to design a complex dynamic system that reacts to any environment, without being pre-programmed on sets of input. The design was relying on fuzzy logic to simulate human emotional reaction, thus increasing the accuracy by further emulating human brain and removing the pre-defined set of input and its matched outputs